2016
DOI: 10.1038/ncomms13220
|View full text |Cite
|
Sign up to set email alerts
|

Direct penetration of spin-triplet superconductivity into a ferromagnet in Au/SrRuO3/Sr2RuO4 junctions

Abstract: Efforts have been ongoing to establish superconducting spintronics utilizing ferromagnet/superconductor heterostructures. Previously reported devices are based on spin-singlet superconductors (SSCs), where the spin degree of freedom is lost. Spin-polarized supercurrent induction in ferromagnetic metals (FMs) is achieved even with SSCs, but only with the aid of interfacial complex magnetic structures, which severely affect information imprinted to the electron spin. Use of spin-triplet superconductors (TSCs) wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 35 publications
7
54
0
Order By: Relevance
“…Its intriguing superconducting ground state, sharing similarities with superfluid 3 He [1][2][3], has attracted much interest and continues to stimulate advances in unconventional superconductivity [4]. Experimental evidence suggest odd-parity spin-triplet pairing, yet questions regarding the proximity of other order parameters, the nature of the pairing mechanism and the apparent absence of the predicted edge currents remain open [3][4][5][6][7][8][9]. Meanwhile, the normal state of Sr 2 RuO 4 attracts interest as one of the cleanest oxide Fermi liquids [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Its intriguing superconducting ground state, sharing similarities with superfluid 3 He [1][2][3], has attracted much interest and continues to stimulate advances in unconventional superconductivity [4]. Experimental evidence suggest odd-parity spin-triplet pairing, yet questions regarding the proximity of other order parameters, the nature of the pairing mechanism and the apparent absence of the predicted edge currents remain open [3][4][5][6][7][8][9]. Meanwhile, the normal state of Sr 2 RuO 4 attracts interest as one of the cleanest oxide Fermi liquids [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…If differing ferromagnetic materials, constituting the left and right F layers are chosen properly, they respond to an external magnetic field in different ways, providing active control of the magnetization misalignment angles through variations in the intensity and direction of an external magnetic field. It was shown that the superconducting transition temperature [46][47][48][49][50] and density of states 13,[51][52][53][54] reveal prominent signatures of the long-ranged spin-triplet superconductivity 5 as a function of magnetization misalignment. Nevertheless, a direct and clear observation of the equal-spin triplet pairings in superconducting hybrids is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Knight shift measurements [12,13] and, recently, proximity-induced superconductivity in epitaxial ferromagnetic SrRuO 6 layers [14] provide strong evidence for triplet pairing. Muon spin rotation [15] and Kerr rotation [16] experiments point to time reversal symmetry breaking at…”
Section: December 2016mentioning
confidence: 99%